Sustainable Design Assesment of Steel Structures - Coşkun, Erdal; SEÇKİN, EDİP (My University, 2019)
Sustainability and environmental factors are becoming essential aspects of the choices of structural materials. In the professional life of modem architects and engineers, sustainable design has become a significant topic. Steel structures are one of the most preferred systems for long-spans and in high-rise buildings by architects and structural engineers. Steel material is also widespread in the building envelope, building services, fasteners, and as concrete elements reinforcement. Inherently high strength and ductility properties of steel have made it a preferred material alternative for many projects. Steel additionally offers other possible sustainable benefits such as efficient construction schedules and lowers construction waste production. On the other hand, steel construction enables durability and recyclability. Steel is the material used in construction that can be recycled many times, without losing its initial properties. Life Cycle Assessment (LCA) is a methodology for addressing the potential impacts of goods and services over their life cycle in an environmental perspective; from raw material and production, to the use and the end-of life phase. Hence, a common interpretation that usually follows the LCA methodology is the “cradle to gate” and "cradle to grave” approach. In the present paper, the sustainability in the field of steel construction discussed, and in order to assess the impact of individual processes within the LCA of the structure, a steel portal frame studied. As a result, the LCA of the steel portal frame confirmed that the environmental impact is directly related to the number of materials used, which affects the processes of the life cycle impact assessment (LCIA).
Keywords: Sustainability; Steel Structures; Portal Frame; Life Cycle Assessment (LCA); LCA Analysis; Sürdürülebilirlik; Çelik Yapılar; Portal Çerçevesi; Yaşam Döngüsü Değerlendirmesi (LCA); LCA Analizi